"Bibijana" - hand care lotion - Dželajlija, Darko; Milošević Georgiev, Andrijana (Archives of Pharmacy, 2022)
Sima T. Joanović was born in Saravola today’s Romania and graduated in pharmacy in Budapest in 1898. After graduating, he worked in Timisoara for a short time. He camed  soon to town of Debeljača and bought the pharmacy "At the Cross" from the pharmacist Ambrozy Sándór, which had been working successfully for more than two decades before that. Sima built a new business and residential building on the then Elisabeth Square and moved the pharmacy into it. He has written articles in cosmetics and perfumery in professional journals. He published his works "What every perfumer should know" in the Pharmaceutical Herald, which helped his colleagues in their work in the field of cosmetics. The pharmacy was widely known for its cosmetic and perfumery products. The first product that made this pharmacy famous "Bibijana" appeared as early as 1905, a non-greasy single-phase lotion based on glycerol, which in a record short time, as printed on the instructions for use, brought even the roughest hand skin in perfect condition. Labels in Hungarian and Serbian were printed for this lotion, which is packed in characteristic 50 ml bottles. The composition of the lotion included: glycerol, ethanol, laurelchery water and perfume in alkaline aqueous solution. The lotion was received with great enthusiasm by the people. It was the first product that was made in bulk. Thanks to the "Bibijana" lotion, the pharmacy became more and more famous, but the other products in the pharmacy were also more and more in demand.